Kebijakan penanganan stunting pada anak usia 24-59 bulan: A scoping review - Ahmad, Nurul Fauziah; Nugraheni, Sri Achadi; Winarni, Sri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Stunting is a condition where a child is physically too short for their age, which can cause problems for both their physical and cognitive abilities in the future. Stunting is known to be caused not only by the characteristics of the toddler but also by various factors, even beyond health, making stunting management policies crucial in overcoming stunting. Purpose: To map policies for managing stunting in children aged 24-59 months. Method: A scoping review was conducted using literature searches in the Science Direct and PubMed Central databases using the keywords